Genetic variation and identification of single nucleotide polymorphism of insulin-like growth factor- 1 gene in Tilapia guineensis - Esther Ukenye; IWALEWA MEGBOWON; OLALEKAN OGUNTADE; TOPE OKETOKI; OLUWAFEMI AMUSA; ADEOLA USMAN; BALKEES SOKENU; RAKIYA ADELEKE; BAWA JOSEPH; CHRISTIAN OMATAH (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ukenye E, Megbowon I, Oguntade O, Oketoki T, Amusa O, Usman A, Sokenu B, Adeleke R, Joseph B, Omatah C. 2020. Genetic variation and identification of single nucleotide polymorphism of insulin-like growth factor- 1 gene in Tilapia guineensis Biodiversitas 21: 5317-5321. Tilapia guineensis is an important cichlid species of West African coastal waters with good nutritional, economic, and aquaculture relevance. The knowledge of the genetic basis of variation in growth traits in Tilapia fish is of great importance to support genetic improvement in the context of aquaculture. In this study, regions of the Tilapia guineensis IGF-1 gene were sequenced, aligned and compared across populations to identify single nucleotide polymorphism and genetic diversity among four populations of T. guineensis in South-west Nigerian coastal waters. A total of thirty-four SNPs were identified across the studied populations and were detected in the forward reaction with twenty-two transversions and twelve transitions. Badagry population showed the highest genetic diversity with the highest molecular diversity indices; number of polymorphic sites, pairwise differences, number of segregating sites and nucleotide diversity while the least diverse population was Pepe. Analysis of molecular variance (AMOVA) revealed that genetic variation was mostly within populations. This finding provides more information regarding variation in insulin growth factor I of T. guineensis and will encourage association study for production traits that will inform useful selection marker for breeding program.